Durability effect on stabilized subgrade soil - Noraida, binti Razali (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Soft clay soil can be categorized as a problematic soil as it has the low strength and high compressibility characteristics. In any highway construction on a soft clay soil, sub-grade soil stabilization is one of the important processes. Therefore, a careful design analysis should be taken for the purposes of any structure built on it. In Sarawak, problematic soils, namely peat, silt and soft clay are the major concern which is inadequate for sub-grade used in the construction of a pavement structure. The focus of this study was mainly the strength and durability of the silty clayey soil. The samples were collected from Kota Samarahan, Sarawak and admixed with cement, fly ash and rubberchip as an additive. The optimum mixture determine from the laboratory is then used as a recommendation for design guideline of sub-grade based on JKR Standard Specification for Road Works and the calculation are performed by using MathCad software. In this study, the stabilized clay specimens were prepared with 5% cement and various fly ash and rubber chips contents, of 5%, 10% and 15%, respectively. The specimens were cured for 7 and 28 days before subjected to Unconfined Compressive Strength (UCS) tests and California Bearing Ratio (CBR) tests. As observed, the stabilization improved the strength and stiffness of the soil properties significantly. However, the addition of 15% rubberchip shows a reduction in strength for both 7 and 28 days curing period. The optimum mixture which fulfilled the JKR Standard Specification was the mixture of 5% cement and 15% fly ash where the value of CBR is 82.6% while the UCS value is 941.69 kPa. However, the mixture of 5% cement and 10% rubberchip can also be used as an alternative to stabilize the sub-grade for low volume road as the CBR value is higher than 30% CBR required by JKR which is 64.66% while the UCS value was 771.77 kPa, respectively.